Prevalence, Etiology and Predictors of Urinary Tract Infections in Febrile Children under the Age of Five Years - Soomro, Tufail; Tikmani, Shiyam Sunder (Infectious Diseases Journal of Pakistan, 2023)
Background: Urinary tract infections (UTI) represent a major burden of infections in children; early diagnosis and appropriate treatment are important to avoid long-term morbidity. In low-middleincome countries, UTI concomitantly presents with other infections. Therefore, this study was done to determine the burden of UTI among febrile children and identify common pathogens and their sensitivity pattern. We also constructed a model that predicts UTI in febrile children. Material and Methods: This was a cross-sectional study conducted at the Pediatric unit, Civil hospital Sukkar from 1st August 2013 to 30th September 2014. Patients up to five years of age of either gender with fever for less than two weeks were enrolled after written consent. Demographic and clinical features were recorded in a proforma. Urine culture was sent within 30 minutes of its collection. Identification of isolates using in-house biochemical tests and susceptibility to commonly used antibiotics was performed using the disc diffusion method. The data was entered and analyzed using SPSS version 20. Results: 272 patients were enrolled in the study. The median age of enrolled children was 2.8 (Interquartile range 2) years. Male patients accounted for 53.3% cases with male to female ratio of 1:1.14. The majority of children presented with low-grade fever, 182 (66.9%) followed by diarrhea (19.5%), dysuria 37 (13.6%), ureteric colic 31 (11.4%) and flank pain 28 (10.3%). Out of them, 32 (11.8%) patients had UTI. E. coli was the most commonly isolated pathogen accounting for 12 cases. Most of the pathogens were sensitive to aminoglycosides, fluoroquinolones, and fosfomycin. Female gender (OR 5.7, 95% CI: 1.88-17.41), diarrhea (OR 7.7, 95% CI: 2.36-28.82) and flank pain (OR 3.67, 95% CI: 1.02-13.21) were independent predictors of urinary tract infection in febrile children. Conclusion: UTI is common among febrile children. Gram negative organisms are common pathogens of UTI and most are still sensitive to conventional antibiotics. Keywords: Febrile children, UTI, Pathogen, Predictors